PENERAPAN MODEL BELAJAR MENGAJAR KOOPERATIF TIPE PROBLEM BASED LEARNING PADA PELAJARAN PENDIDIKAN AGAMA ISLAM - Sulistiyowati Sulistiyowati; Illyas Thohari; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Cooperative Learning Model Type Problem Based Learning is a learning model which uses problems to stimulate students and learn to solve problems in groups so as to increase students' knowledge and skills according to the achievement of learning objectives. The application of cooperative learning model type of problem based learning in Islamic Religious Education can create interesting and fun learning. Cooperative learning model type of problem based learning is the teacher's effort to create creative, innovative and communicative learning in order to make students become independent in developing the potential of critical thinking skills, and to be able to solve problems provided by the teacher. The focus of research includes planning learning, techniques for implementing learning and evaluating cooperative learning models of problem based learning types. The research method uses qualitative research. Data collection uses interview, observation and documentation techniques. In the implementation of learning the teacher must prepare a learning plan and apply it in the learning process and carry out assessments by covering cognitive, affective and psychomotor aspects.